Precision of dimensional measurements of mandible in different positions on orthopantomogram - Honey Arora; Vibha Jain; Keerthilatha M Pai; Raman Kamboj (Wolters Kluwer Medknow Publications, 2013)
Objective: To evaluate the precision of dimensional measurements of the mandible in two different positions on orthopantomogram (OPG) (one with mandibular plane parallel to the floor and the other with Frankfort horizontal plane parallel to the floor) and determine the dimensional reliability. Materials and Methods: Anatomical landmarks were used to denote points for measurements on mandible as well as OPG and respective measurements made. Magnification was hence calculated and compared with magnification factor (1.2) listed by the manufacturer. Results: Vertical measurements and anterior horizontal and oblique measurements showed minimal magnification. Posterior horizontal and oblique measurements showed increased magnification. The difference in measurements in the two positions and on comparison with the one given by the manufacturer was statistically significant for posterior horizontal measurements but not for posterior oblique. Horizontal measurements crossing the midline were highly magnified and the difference was statistically significant for the two positions and on comparison to the one given by manufacturer. Conclusion: Magnification factor given by the manufacturer is not uniform in all locations and varies with changes in positioning and hence should not be relied upon when accurate measurements are to be made.